Minimally invasive surgery versus laparotomy for radical hysterectomy in the management of early-stage cervical cancer: survival outcomes - Brandt, Benny (Gynecol Oncol, 2020)
OBJECTIVE: To compare oncologic and perioperative outcomes in patients who underwent minimally invasive surgery (MIS) compared to laparotomy for newly diagnosed early-stage cervical carcinoma. METHODS: We retrospectively identified patients who underwent radical hysterectomy for stage IA1 with lymphovascular invasion (LVI), IA2, or IB1 cervical carcinoma at our institution from 1/2007–12/2017. Clinicopathologic characteristics and surgical and oncologic survival outcomes were compared using appropriate statistical testing. Multivariable Cox regression analysis was used to control for potential confounders. RESULTS: We identified 196 evaluable cases—117 MIS (106 robotic [90.6%]) and 79 laparotomy cases. Cohorts had similar age, BMI, substage, histologic subtype, clinical and pathologic tumor size, positive margins, and presence of LVI. The MIS group had more cases with no residual tumor in the hysterectomy (24.8% vs. 10.1%, P=0.01). The laparotomy group had more cases with positive nodes (29.1% vs. 17.1%, P=0.046) and more patients who received adjuvant therapy (53.2% vs. 33.3%, P=0.006). Median follow-up was ~4 years. Five-year disease-free survival (DFS) rates were 87.0% in the MIS group and 86.6% in the laparotomy group (P=0.92); 5-year disease-specific survival (DSS) rates were 96.5% and 93.9%, respectively (P=0.93); and 5-year overall survival (OS) rates were 96.5% and 87.4%, respectively (P=0.15). MIS was not associated with DFS, DSS, or OS on multivariable regression analysis. The rate of postoperative complications was significantly lower in the MIS cohort (11.1% vs. 20.3%; P=0.04). CONCLUSIONS: MIS radical hysterectomy for cervical carcinoma did not confer worse oncologic outcomes in our single-center and concurrent series of patients with early-stage cervical carcinoma.